Factor generating construction waste materials on site - Nur Fatihah, Mohd Solahuddin (2018)
Rapid growth in construction activities increases construction waste problems around the world. The generation of construction waste could give negative impact to the construction project. In order to reduce the negative impact, it is needed to identify the cause that effecting the waste generation. The aim of this research is to identify the most significant factor contribute to the construction waste generation at site. This research outcome will provide understanding about the types of construction waste generate on site, factor affecting the construction waste generated and the most significant factor that contribute to the construction waste materials generate. Based on the past researcher and literature review, the factors that affecting the construction waste generation were grouped into five categories: Design, Handling, Workers, Management and Procurement. The data and information were collected by distributed the questionnaire survey to the construction workers that are registered with CIDB (Construction Industry Development Board) or PKK (Pusat Khidmat Kontraktor). The data obtained were analysed using Relative Importance Indices (RII) and were ranked based on their group. From the result and data analysis, the highest ranked as indicated by most researchers was design factor that contributes to large generation of construction waste. Meanwhile, the second highest factor were workers, followed by handling, management and procurement. Through identifying the important causes, construction industries players can avoid and alert about how the waste was generated. It will gives a great benefit for country in term of protection of the environment, economic and society.